Establishing The Personality Of The Young Generation Through Musabaqah Activities At Dayah Markaz Al-Ishlah Al-Aziziyah Lueng Bata Banda Aceh City - Nurbayani, Nurbayani (Cita konsultindo, 2023)
Musabaqah activities at the Dayah Markaz Al-Ishlah Al-Aziziyah Lueng Bata City of Banda Aceh for the younger generation can influence the personality of the younger generation. Personality includes all thoughts, feelings and behavior, conscious and unconscious. Personality guides people to adjust to the social and physical environment. From the beginning of life, the personality is a unit or has the potential to form a unit. When developing personality, one should try to maintain unity and harmony among all the elements of personality. Personality development at Dayah Markaz Al-Ishlah Al-Aziziyah Lueng Bata Banda Aceh City is carried out regularly and is directed so that students can develop and practice it in everyday life. To achieve this goal is certainly inseparable from several supporting factors that are available and implemented properly, such as good teaching staff and other factors that influence the process of personality development as a whole. Optimizing the role of the administrators of Dayah Markaz Al-Ishlah Al-Aziziyah Lueng Bata Banda Aceh City in developing the personality of the younger generation is very important, in line with the demands of the times. Dayah Markaz Al-Ishlah Al-Aziziyah Lueng Bata Banda Aceh City should also understand the institution's position in society, recognize community agencies and institutions that support education, recognize social and economic changes, all of which must be accompanied by IMTAQ and Science and Technology, in order to realize the morals, behavior and personality of the nation's children as potential successors to our nation.